Focused Shockwave Treatment for Greater Trochanteric Pain Syndrome: A Multicenter, Randomized, Controlled Clinical Trial. (5th August 2020) - Ramon, Silvia; Russo, Sergio; Santoboni, Flavia; Lucenteforte, Giacomo; Di Luise, Carla; de Unzurrunzaga, Rocio; Vetrano, Mario; Albano, Mariantonia; Baldini, Rosella; Cugat, Ramon; Stella, Giulia; Balato, Giovanni; et al.
Abstract : Background: Greater trochanteric pain syndrome (GTPS) is a condition of lateral hip pain. Its physiopathology remains unknown, and there is no consensus on optimal management. The aim of this study was to assess the effectiveness of electromagnetic-focused extracorporeal shockwave treatment (F-ESWT) in patients with GTPS. Methods: This multicenter clinical trial included 103 patients with chronic GTPS randomly assigned to the treatment group, consisting of electromagnetic F-ESWT and a specific exercise protocol, or the control group, receiving sham F-ESWT and the same exercise protocol. Both groups were treated with 3 weekly sessions; the F-ESWT group received an energy flux density of 0.20 mJ/mm 2, whereas the control group received 0.01 mJ/mm 2 . Patients were assessed at baseline and 1, 2, 3, and 6 months after treatment. A visual analogue scale (VAS) score for pain at 2 months was the primary outcome. The Harris hip score (HHS), Lower Extremity Functional Scale (LEFS), EuroQoL-5 Dimensions Questionnaire (EQ-5D), and Roles and Maudsley score were used as secondary outcomes. Complications were recorded. Results: The mean VAS score decreased from 6.3 at baseline in both groups to 2.0 in the F-ESWT group versus 4.7 in the control group at 2 months; the 2-month score differed significantly between groups (p < 0.001). All secondary outcomes at all follow-up intervals were significantly better in the F-ESWT group, except for the LEFS score at 1 month after treatment (p = 0.25). No complications were observed. Conclusions: F-ESWT in association with a specific exercise program is safe and effective for GTPS, with a success rate of 86.8% at 2 months after treatment, which was maintained until the end of follow-up. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.